Behaviour of the interface between stored wheat and a steel silo under static and cyclic loading conditions. (February 2020) - Zeng, Changnv; Li, Xuetong; Wang, Yuke
Abstract : The interface behaviour between the steel surfaces of a silo and the grains wheat stored within plays a decisive role in the design of the structure of the silo. A series of strain-controlled direct shear tests, including monotonic loading, cyclic loading and post-cyclic loading were used to study the behaviour of the wheat-steel interface behaviour. The influence of cycle numbers, shear displacement amplitude, normal stress and initial void ratio on the behaviour of the interface behaviour are examined in detail. It was observed that the cyclic loading results in an increasing peak strength, internal friction angle and apparent cohesion, whereas decreasing interface contraction deformation occurs. The results show that the values of peak stress increase with increasing displacement amplitude and cycles, and they change slightly after 10 cycles. The interface exhibits overall contraction, while the contraction is suppressed by an alternating small dilation during cyclic loading. The ultimate peak shear strength increases with increasing normal stress and decreasing initial void ratio. During the tests, the interfaces displayed larger contraction at higher normal stresses and initial void ratios. These findings provide useful information for the analysis of the wheat-steel interface behaviour during both static and cyclic loading conditions. Highlights: The mechanical properties of wheat in silos are investigated. Tests were conducted on wheat by using a developed new direct shear test apparatus. Strain-controlled monotonic, cyclic and post-cyclic direct shear tests were conducted to investigate the wheat-steel interface behavior.